Microwave Models for Graphene Ambipolar Devices: An Engineering Teaching Perspective - Pasadas, Francisco; Medina-Rull, Alberto; Marín, Enrique G. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
In this article it iimplemented a set of circuit models to be exploited in conventional circuit simulators used in engineering degrees. The models capture the physics of the graphene-based transistors, characterized by the ambipolar conduction, and its resulting V-shaped transfer characteristics (current vs. gate voltage). These models can be exploited by the engineering students to explore ambipolar electronics opening the possibility to 1) redesigning and simplifying of conventional circuits; and 2)seeking of new functionalities in both analogue/RF and digital domains. In thisregard, as an example by just considering that the V-shaped transfer characteristicsbehaves as a parabola, we present new insights for the design of graphene-based RFpower amplifiers, mixers, phase shifters and frequency multipliers that specifically